2017
DOI: 10.3389/fphar.2017.00192
|View full text |Cite
|
Sign up to set email alerts
|

Oriental Medicine Samhwangsasim-tang Alleviates Experimental Autoimmune Encephalomyelitis by Suppressing Th1 Cell Responses and Upregulating Treg Cell Responses

Abstract: Oriental medicine Samhwangsasim-tang (SHSST) has traditionally been used in East Asia to treat hypertension and its complications. However, little is known about its potential value regarding the treatment of chronic inflammatory diseases such as multiple sclerosis (MS). In this study, we investigated whether SHSST has a beneficial effect in treating myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis (EAE). Onset-treatment with SHSST was found to alleviate neurological sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 63 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…Ten studies evaluated the neuroprotective effects induced by crude extracts obtained from plants ( Sekiya et al, 2009 ; Guimarães-Santos et al, 2012 ; Badem et al, 2014 ; Zhang et al, 2015 ; Lee et al, 2017 ; Li et al, 2018 ; Martinez-Oliveira et al, 2018 ; Zhou et al, 2018 ; Huang et al, 2019 ; Kim et al, 2020 ), 2 studies used isolated molecules ( Kyung et al, 2006 ; Zhu et al, 2006 ), and 2 studies reported the effect of a compound ( Chen et al, 2012 ; Zhou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies evaluated the neuroprotective effects induced by crude extracts obtained from plants ( Sekiya et al, 2009 ; Guimarães-Santos et al, 2012 ; Badem et al, 2014 ; Zhang et al, 2015 ; Lee et al, 2017 ; Li et al, 2018 ; Martinez-Oliveira et al, 2018 ; Zhou et al, 2018 ; Huang et al, 2019 ; Kim et al, 2020 ), 2 studies used isolated molecules ( Kyung et al, 2006 ; Zhu et al, 2006 ), and 2 studies reported the effect of a compound ( Chen et al, 2012 ; Zhou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The crude extracts, compounds, and/or isolated molecules were extracted from herbs in 4 studies, roots in 4 studies, leaves in 2 studies, rhizomes in 2 studies, fruit in 2 studies, flower in 1 study, tree in 1 study, and trunk in 1 study. Among the experimental models, 4 studies induced spinal cord injury ( Kyung et al, 2006 ; Chen et al, 2012 ; Zhang et al, 2015 ; Zhou et al, 2020 ), 5 studies analyzed multiple sclerosis ( Zhu et al, 2006 ; Lee et al, 2017 ; Li et al, 2018 ; Huang et al, 2019 ; Kim et al, 2020 ), 2 studies evaluated amyotrophic lateral sclerosis ( Sekiya et al, 2009 ; Zhou et al, 2018 ), 1 study induced spinal cord ischemia ( Badem et al, 2014 ), 1 study reproduced acute damage to the motor cortex ( Guimarães-Santos et al, 2012 ), and 1 study replicated Alzheimer-like disease damage in the hippocampus ( Martinez-Oliveira et al, 2018 ). Ten in vivo studies, 1 in vitro study, and 3 both in vivo and in vitro studies were selected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations